Chloroform compatible, thiol-ene based replica molded micro chemical devices as an alternative to glass microfluidic chips. Issue 5 (28th January 2019) - Geczy, Reka; Sticker, Drago; Bovet, Nicolas; Häfeli, Urs O.; Kutter, Jörg P.
Abstract : We render thiol-ene polymers exceptionally solvent resistant by applying heat post-fabrication. The method is simple, effective, and universal for various thiol-enes and solvents. Abstract : Polymeric microfluidic chips offer a number of benefits compared to their glass equivalents, including lower material costs and ease and flexibility of fabrication. However, the main drawback of polymeric materials is often their limited resistance to (organic) solvents. Previously, thiol-ene materials were shown to be more solvent resistant than most other commonly used polymers; however, they still fall short in "harsh" chemical environments, such as when chlorinated solvents are present. Here, we show that a simple yet effective treatment of thiol-ene materials results in exceptional solvent compatibility, even for very challenging chemical environments. Our approach, based on a temperature treatment, results in a 50-fold increase in the chloroform compatibility of thiol-enes (in terms of longevity). We show that prolonged heat exposure allows for the operation of the microfluidic chips in chloroform for several days with no discernable deformation or solvent-induced swelling. The method is applicable to many different thiol-ene-based materials, including commercially available formulations, and also when using other commonly considered "harsh" solvents. To demonstrate the utility of the solvent compatible thiol-enes for applications where chloroform is frequently employed, we show the continuous and uniform production of polymeric microspheres for drug delivery purposes over a period of 8 hours. The material thus holds great promise as an alternative choice for microfluidic applications requiring harsh chemical environments, a domain so far mainly restricted to glass chips.